Compatibility academic among master’s students at the Faculty of Social Sciences, Ibn Khaldoun University - Tiaret in light of the Corona virus pandemic - bouchrit, nouria (Journal of Social Sciences and Humanities, 2023)
The present study aimed at recognizing the level of academic Compatibility among master’s students at the Faculty of Social Sciences, Ibn Khaldoun University, Tiaret , it aimed at determining the differences in level in regard to the difference in gender , and the Specialization, and the the year. The researcher adopted the descriptive method through the application of the YOUNGMAN Scale of Academic adjustment, which consists of three dimensions, Afer being sure of it psychometric features. The study was applied on a sample group of 500 students, after processing the data statistically, the study reached the following results: The level of academic Compatibility among students of the Faculty of Social Sciences at Ibn Khaldun University is above average. There are statistically significant differences in level of academic Compatibility among students of the Faculty of Social Sciences at Ibn Khaldun University in what regards the variable of the gender. There are statistically significant differences in level of academic Compatibility among students of the Faculty of Social Sciences at Ibn Khaldun University in what regards the variable of the year. There are no statistically significant differences in level of academic Compatibility among students of the Faculty of Social Sciences at Ibn Khaldun University in what regards the variable of the Specialization. The results were discussed on the basis of literature review, previous studies, and on the basis sample characterics